The Role of Stromal Proteolytic Systems in Cancer Progression (Review) - E. V. Kugaevskaya; O. S. Timoshenko; T. A. Gureeva; N. I. Solovieva (Общая реаниматология)
Oncological diseases belong to life-threatening pathologies being the second most frequent cause of morbidity and mortality after cardiovascular diseases. Clarification of carcinogenesis mechanisms makes it possible to expand the stock of tools available for prevention of critical illness accompanying this pathological condition.Nowadays, proteolytic systems of tumor microenvironment (ТМЕ) are regarded as key regulators of a tumor progression including tumor growth, invasion and metastazing. The review discusses ТМЕ structure and role in cancer progression.Recent data decipher the role of proteolytic systems in the interaction stromal cells with tumor cells in different types of cancer in humans. The most known proteolytic systems contributed to cancer progression are matrix metalloproteinase system (MMP), urokinase-type plasminogen activator system (uPA-system), various cathepsins, granzymes, and elastase. Inhibition of extracellular proteolysis in the course of an oncological process is considered an effective approach to cancer therapy.